Long-term In vitro Expansion Alters the Biology of Adult Mesenchymal Stem Cells - Izadpanah, Reza (2008)
Mesenchymal stem cells (MSC) derived from bone marrow stem cells (BMSC) and adipose tissue stem cells (ASC) of humans and rhesus macaques were evaluated for their cell cycle properties during protracted culture in vitro. Human ASCs (hASC) and rhesus BMSCs (rBMSC) underwent significantly more total population doublings than human BMSCs (hBMSC) and rhesus ASCs (rASC). The cell cycle profile of all MSCs was altered as cultures aged. hMSCs underwent an increase in the frequency of cells in the S phase at P20 and P30. However, rhesus MSCs from both sources developed a distinct polyploid population of cells at P20, which progressed to aneuploidy by P30. Karyotype analysis of MSCs revealed the development of tetraploid or aneuploid karyotypes in the rhesus cells at P20 or P30. Analysis of the transcriptome of the MSCs from early and late passages revealed significant alterations in the patterns of gene expression (8.8% of the genes were differentially expressed in hBMSCs versus hASCs, and 5.5% in rBMSCs versus rASCs). Gene expression changes were much less evident within the same cell type as aging occurred (0.7% in hMSCs and 0.9% in rMSC). Gene ontology analysis showed that functions involved in protein catabolism and regulation of pol II transcription were overrepresented in rASCs, whereas the regulation of IκB/nuclear factor-κB cascade were overrepresented in hBMSCs. Functional analysis of genes that were differentially expressed in rASCs and hBMSCs revealed that pathways involved in cell cycle, cell cycle checkpoints, protein-ubiquitination, and apoptosis were altered.